2021
DOI: 10.1016/j.sjbs.2020.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Partial substitution of organic nitrogen with synthetic nitrogen enhances rice yield, grain starch metabolism and related genes expression under the dual cropping system

Abstract: Improving grain filling in the presernt farming systems is crucial where grain filling is a concern due to the extreme use of chemical fertilizers (CF). A field experiment was conducted at the experimental station of Guangxi University, China in 2019 to test the hypothesis that cattle manure (CM) and poultry manure (PM) combined with CF could improve rice grain filling rate, yield, biochemical and qualitative attributes. A total of six treatments, i.e., no fertilizer (T 1 ), 100% CF (T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…However, organic manure is relatively low in nutrient content, and its release rate is generally too slow to meet plant requirements in a short time period. Thus, the combined application of organic manure and CF has proven to be a promising option in improving and maintaining soil fertility and crop production than the use of either amendments or alone 20 , 22 . Although the advantages of organic manure fertilization are generally recognized, its optimal application ratio with CF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, organic manure is relatively low in nutrient content, and its release rate is generally too slow to meet plant requirements in a short time period. Thus, the combined application of organic manure and CF has proven to be a promising option in improving and maintaining soil fertility and crop production than the use of either amendments or alone 20 , 22 . Although the advantages of organic manure fertilization are generally recognized, its optimal application ratio with CF remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A higher amylose content may be associated with fertilizer application. Iqbal et al reported that the use of an organic fertilizer combined with a chemical fertilizer considerably improved the rice amylase content [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The appropriate use of N fertilizer is key for meeting the demand of the growing human population Accepted paper for food and soil for improving soil health and cereals crop quality (Izhar et al 2020a;Iqbal et al, 2020b;Ullah et al, 2020). However, the overuse of chemical N fertilizer can lead to several problems, such as environmental pollution, soil degradation, water contamination, and decreased crop productivity (Cai et al, 2018;Peng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%